2009
DOI: 10.1590/s1516-80342009000200012
|View full text |Cite
|
Sign up to set email alerts
|

A ocorrência de ceceio em crianças de oito a 11 anos em escolas municipais

Abstract: OBJETIVOS: Verificar a ocorrência de ceceio em crianças de oito a 11 anos das escolas municipais de Itaqui/RS, de acordo com sexo e faixa etária, além de verificar a associação do ceceio com possíveis fatores de risco, tais como hábitos de sucção (chupeta, dedo e mamadeira) até os seis anos de idade, má oclusão dentária, respiração oral e praxias de língua. MÉTODOS: Foi realizado um estudo observacional, exploratório, contemporâneo, prospectivo e de grupo, por meio de questionário com os responsáveis e de aval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 7 publications
3
17
0
9
Order By: Relevance
“…The results further indicate that words composed of unvoiced alveolar fricative may favor the onset of therapy (because they allow greater perception of deviations in the production), while words composed of voiced alveolar fricative may be used at later periods, since they are syllable contexts that seem more difficult to monitor during 8 months) with operated cleft lip and palate 18 . The present findings also agree with previous information in the literature 10,14 for children without craniofacial malformations, in which lisping was not observed in all preschool children with malocclusion. In these studies, the presence of morphological alterations (malocclusion) was considered a factor that favors the presence of lisping, yet it should not be considered determinant.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results further indicate that words composed of unvoiced alveolar fricative may favor the onset of therapy (because they allow greater perception of deviations in the production), while words composed of voiced alveolar fricative may be used at later periods, since they are syllable contexts that seem more difficult to monitor during 8 months) with operated cleft lip and palate 18 . The present findings also agree with previous information in the literature 10,14 for children without craniofacial malformations, in which lisping was not observed in all preschool children with malocclusion. In these studies, the presence of morphological alterations (malocclusion) was considered a factor that favors the presence of lisping, yet it should not be considered determinant.…”
Section: Discussionsupporting
confidence: 93%
“…However, so far, there is no information on possible differences in the articulatory characteristics of fricatives [s] and [z] in the presence of lisping in children with cleft lip and palate, as well as whether these characteristics may be perceived and/or influence the auditory perceptual judgment of lisping. The hypothesis initially adopted in this study is that lisping, when present, presents differently in voiced and unvoiced fricatives, with greater occurrence indicated that occlusal changes may cause damage to the production of alveolar fricative consonants 1,[8][9][10][11][12] , even though this relationship is not always observed 13 or even may not be directly related to the severity of occlusal alteration 14 . Some such studies investigated the occurrence of lisping when produced in words or other speech samples composed of alveolar consonants ([s] and/or [z]) 8,9,12,13 .…”
Section: Considering That Differences Between Fricativesmentioning
confidence: 99%
“…When those structures present tonicity and praxis alterations, they may interfere in the phonemes production [5][6][7] . So, the articulatory imprecision also may contribute to this situation 8,9 , because speech requires complex coordination and planning of lips and tongue movements to produce sounds [10][11][12][13] . Thus, there is a common neurophysical connection between the speech planning and the fine motor, which are altered in children with PD…”
Section: Study Accomplished At Centro De Estudos De Linguagem E Fala mentioning
confidence: 99%
“…In addition, 4.2% of children had both phonetic and phonological changes (25) . In general, studies report an association between the presence of phonetic deviation and motor orofacial changes (25,28) . Others have shown that the production of /s/, phoneme that showed changes in our sample, requires precise operating conditions and forms of orofacial structures because it has an articulation point more stable and therefore does not allow multiple articulatory trajectories to achieve the same socket.…”
Section: Discussionmentioning
confidence: 99%
“…Other findings observed in the sample, which may also contribute to the phonetic changes described are the anterior open bite and the increased overbite. The open bite may lead to adjustments in tongue positioning, inserting it, protracting it or raising it (28) , as well as the overbite, which reduces the intraoral space due to the decrease of the vertical dimension, which may hinder the necessary movements of the tongue in speech production (24) . Central nervous system abnormalities constitute the most serious complications of IP (2,3) .…”
Section: Discussionmentioning
confidence: 99%